Saccharin: an efficient organocatalyst for the one-pot synthesis of 4-amidocinnolines under metal and halogen-free conditions - Khaligh, Nader Ghaffari; Mihankhah, Taraneh; Johan, Mohd Rafie; Juan, Joon Ching (Springer Verlag, 2018)
A mild and efficient protocol for the one-pot synthesis of 4-amidocinnolines was developed using saccharin as a cheap and eco-friendly organocatalyst and t-butyl nitrite as a metal-free diazotization reagent. The current method has advantages such as cost effectiveness, use of the biodegradable reagents, simple experimental procedure; afford the quantitative yield of the desired products, metal- and halogen-free as well as environmentally benign conditions.